Pengaruh Brand Ambassador dan Citra Merek Terhadap Minat Beli Konsumen Produk Body Lotion Scarlett Di Kota Medan - Natalia Hutabarat; Anne Rumondang Malau (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2022)
The purpose of this study was to determine and analyze the influence of brand ambassadors and brand image on consumer buying interest in Scarlett body lotion products in Medan City. The population in this study are consumers who are interested in buying Scarlett body lotion products in Medan City. Data were collected using distributing online questionnaires. After collecting data, the sample used in this study amounted to 100 respondents, using purposive sampling method with non-probability sampling technique. The results of the analysis show that brand ambassadors and brand image have a positive and significant effect on buying interest. The type of research used in this research is quantitative research. The data analysis used is Analysis Equation Modeling (SEM) using Smart-PLS 3.0 software.